Cooperating embedded systems and wireless sensor networks (ISTE/John Wiley, 2008)
The first part of the book covers cooperating object applications and the currently available application scenarios, such as control and automation, healthcare, and security and surveillance. The second part discusses paradigms for algorithms and interactions. The third part covers various types of vertical system functions, including data aggregation, resource management and time synchronization. The fourth part outlines system architecture and programming models, outlining all currently available architectural models and middleware approaches that can be used to abstract the complexity of cooperating object technology.